Development of a Bioavailable μ Opioid Receptor (MOPr) Agonist, δ Opioid Receptor (DOPr) Antagonist Peptide That Evokes Antinociception without Development of Acute Tolerance - Mosberg, Henry I. (American Chemical Society, 2014)
[Image: see text] We have previously described a cyclic tetrapeptide, 1, that displays μ opioid receptor (MOPr) agonist and δ opioid receptor (DOPr) antagonist activity, a profile associated with a reduced incidence of opioid tolerance and dependence. Like many peptides, 1 has poor bioavailability. We describe here an analogue of 1 with an added C-terminal β-glucosylserine residue, Ser(β-Glc)NH(2), a modification that has previously been shown to improve bioavailability of opioid peptides. The resulting peptide, 4, exhibits full antinociceptive efficacy in the mouse warm water tail withdrawal assay after intraperitoneal administration with potency similar to that of morphine. Further, 4 does not give rise to acute tolerance and thus represents a promising lead for the development of opioid analgesics with reduced side effects.